Urgensi pengajaran information literacy pada tingkat perguruan tinggi - Ida Farida (Al Maktabah, 2006)
The advance of information technologies has brought tremendous impact in library service at higher education. This situation give the fact that library should give information literacy teaching for students to support their academic performance. Association of College and Research Libraries (ACRL), has determined competency standards of information Literacy for higher education. These competency standards consist of 5 standards and 24 performance indicators which can be used as guidance for any librarian in academic library to develop information literacy program. Tertiary Educational institutions in Indonesia which are not isolated from the changes occurred globally should respond with this trend that is teaching information literacy for the students. Several obstacles that hinder the program of information literacy in academic library in Indonesia are discussed. The obstacles should be figure out systematically in order to enhance our educational qualities in the future.Kata Kunci: Information literacy, perguruan tinggi